„Light sedation" strategy vs. deep sedation in mechanically ventilated patients: An analysis of clinical outcomes and safety - Kobylińska, Julia; Krzysiak , Katarzyna; Skoczko, Zuzanna; Zieliński , Daniel (Quality in Sport, 2026)
Background. Sedation management is a cornerstone of supportive care for critically ill patients receiving mechanical ventilation. While deep sedation was historically the standard, contemporary practices are shifting toward an "eCASH" model (Comfort and patient-centered Care without excessive Sedation and High levels of analgesia). Aim. The objective of this study was to comprehensively evaluate and compare clinical outcomes between light sedation and deep sedation strategies in mechanically ventilated patients, focusing on mortality rates, duration of mechanical ventilation, length of stay (LOS), and neurological complications. Material and methods. A detailed analysis was performed based on 40 scientific sources, including randomized controlled trials and meta-analyses. Sedation depth was primarily defined using the Richmond Agitation-Sedation Scale (RASS). Results. Early deep sedation (within 48 hours) is an independent predictor of increased mortality (Hazard Ratio = 1.661). Light sedation was associated with a reduction in mechanical ventilation duration by an average of 2.1 days and shorter ICU stays by 3 days. Conclusions. Targeting light sedation should be the default standard of care to improve patient survival and recovery, as deep sedation is a strong predictor of delirium and increased mortality.